2009
DOI: 10.1093/her/cyp002
|View full text |Cite
|
Sign up to set email alerts
|

Planned, motivated and habitual hygiene behaviour: an eleven country review

Abstract: Handwashing with soap (HWWS) may be one of the most cost-effective means of preventing infection in developing countries. However, HWWS is rare in these settings. We reviewed the results of formative research studies from 11 countries so as to understand the planned, motivated and habitual factors involved in HWWS. On average, only 17% of child caretakers HWWS after the toilet. Handwash ‘habits’ were generally not inculcated at an early age. Key ‘motivations’ for handwashing were disgust, nurture, comfort and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
447
4
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(481 citation statements)
references
References 38 publications
26
447
4
4
Order By: Relevance
“…However, many studies have moved away from the simple assumption that knowledge about germs and diseases can change or affect attitudes and behaviours. 9 The Theory of Planned Behaviour 25 or extension theory 16 including cognitive and environmental factors were used, and motivation was the focus of the behaviour discussion in these studies. This model is more comprehensive in explaining behaviour formation and change, which could be the direction of future research and studies.…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many studies have moved away from the simple assumption that knowledge about germs and diseases can change or affect attitudes and behaviours. 9 The Theory of Planned Behaviour 25 or extension theory 16 including cognitive and environmental factors were used, and motivation was the focus of the behaviour discussion in these studies. This model is more comprehensive in explaining behaviour formation and change, which could be the direction of future research and studies.…”
Section: Characteristicsmentioning
confidence: 99%
“…A survey 9 undertaken by the Global PublicePrivate Partnership for Handwashing in five Sub-Saharan African countries indicated that only 17% of children's caregivers washed their hands with soap after defaecation. In rural Shaanxi province, Zhao et al 10 reported that 40.0% of residents washed their hands before eating and 19.2% did so after toilet use.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also important to mention the extensive literature that exists showing that knowledge alone is often not sufficient to change behavior and that contextual, psychosocial, and technological factors all play a role in facilitating water, sanitation, and hygiene behavior change. [32][33][34][35][36] Effective interventions to target previously identified knowledge and behavioral risk factors for diarrheal disease in children include promotion of hand washing with soap, hygiene education, latrine installation at the household and community level, municipal water connection, water kiosk, householdbased chlorination, filtration, solar disinfection, and improved water storage. [37][38][39][40] However, risk factors for childhood diarrhea vary by population with some factors being more important than others in particular settings.…”
Section: Introductionmentioning
confidence: 99%
“…Influence of norms has been demonstrated empirically. Drawing on Cialdini's definitions, researchers have demonstrated the influence of social norms on several health-related practices, including: alcohol consumption [45,46], food intake [47], use of recreational drugs [48,49], smoking [50], water purification [51], and hand washing [52].…”
Section: Introductionmentioning
confidence: 99%